THE ROLE OF PHARMACISTS IN MITIGATING MEDICATION ERRORS IN GERIATRIC PATIENTS A SINGLE CENTER STUDY - Sadaf Shamshad; Hasib Shamshad (Journal of Population Therapeutics and Clinical Pharmacology, 2020)
Objectives: The multifaceted study aims to quantify markers of pharmacist effectiveness in medication mistake abatement among elderly people through interventions at the Lady Reading Hospital in Peshawar over six months. Study design: A prospective observational study.Place and duration of study: The esteemed Department of Pharmacy at Lady Reading Hospital, Peshawar, from January to July 2019. Methods: a prospective observational study. Clinical pharmacists clinically investigated the drug plans of 200 geriatric patients meticulously, keeping a defrauder record of medication errors medication-related issues, and episodes of pharmacist intervention nations in all details and transparencies. To dig deeper another descriptive section was used to summarize the information in the units and reveal frequencies, rates, and top and low gravity subjects. It also included standard deviation measures for constant factors. Patient outcomes related to the provision of pharmacist interventions were studied in terms of the drop in the incidence of medication errors and the acceptance level of doctors' proposals. Results: Among the 200 patients, we identified a total of 380 medication-related problems. This means that on average, each patient had 1. 90 such issues. The most common problems were about medication effectiveness, unnecessary drug treatments, and missed or double dosages. Pharmacists were involved in 670 cases, in which 41% of interactions were carried out at the level of endorsements. Impressively, 91. 7% of the suggestions were taken into account by the doctors, leading to 65. 8% of drug-related problems are terminated. It was a clear demonstration of the critical role pharmacists have played in improving drug health and effectiveness for the elderly at LRH. Conclusion: the role of pharmacists in reducing medication errors among older patients was greatly demonstrated. This demonstrated how pharmacists play a crucial role in improving medication safety and in bettering health outcomes.